Social Carrying Capacity of Tourism Development at Tanjung Benoa Beach, Badung Regency - Wiranta, Made (Unit Pelayanan Bahasa, Politeknik Pariwisata Bali, 2023)
Social Carrying Capacity is the response or reaction of the local community to the development of tourism in an area. Tanjung Benoa is a very popular tourist attraction among tourists who like water sports activities. However, the Covid-19 pandemic or better known as the Corona Virus is currently sweeping the world. The tourism industry is an industry that has been greatly affected by this pandemic. Declining tourist visits can have an impact on a destination, both in economic, socio-cultural, and environmental aspects. This study aims to determine whether the social carrying capacity at Tanjung Benoa Tourist Attraction has been exceeded or not. The data in this study were collected through questionnaires in six neighborhoods in Tanjung Benoa. Questionnaires were distributed to 100 respondents with a total of 35 indicators. The sampling technique in this study used Probability Sampling with the type of Proportionate Stratified Random Sampling which was then analyzed using descriptive statistics. Based on the research results, it is known that the social carrying capacity at Tanjung Benoa Tourist Attraction has not been exceeded. Local people still want tourism activities in Tanjung Benoa